World-smallest fiber-GRIN lens system for optofluidic applications - Filipkowski, Adam; Piechal, Bernard; Pysz, Dariusz; Stepien, Ryszard; Cimek, Jarosław; Waddie, Andrew; Klimczak, Mariusz; Stafiej, Paulina; Taghizadeh, Mohammad R.; Buczynski, Ryszard (Photonics Letters of Poland, 2016)
We have developed a new type of an optical fiber probe which integrates the standard single mode fiber with a gradient index (GRIN) microlens. The system is perfectly suited for optofluidic sensor applications since the diameter of the lens module is exactly the same as the diameter of the optical fiber. Moreover, the performance of the GRIN lens is not degraded by low contrast of the refractive index between of the lens and the fluidic environment. The GRIN lens is made with novel technology of nanostructured optics. Full Text: PDF References M. Woerdemann, C. Alpmann, M. Esseling, C. Denz, "Advanced optical trapping by complex beam shaping", Laser Photonics Rev. 7, 839 (2013). CrossRef E. Weber, F. Keplinger, and M. J. Vellekoop, "On-Chip Light Modulation Applying Optofluidic Principles", IEEE Sensors Journal 13 4773 (2013). CrossRef F. Hudelist, J. M. Nowosielski, R. Buczynski, A. J. Waddie, M. R. Taghizadeh, "Nanostructured elliptical gradient-index microlenses", Optics Letters 35, 130 (2010) CrossRef J. M. Nowosielski, R. Buczynski, F. Hudelist, A. J. Waddie, M. R. Taghizadeh, "Nanostructured GRIN microlenses for Gaussian beam focusing", Opt. Comm. 283 1938 (2010). CrossRef A.Sihvola, Electromagnetic Mixing Formulas and Applications (London: The Institution of Electrical Engineers 1999). J. Nowosielski, R. Buczynski, A. J. Waddie, A. Filipkowski, D. Pysz, A. McCarthy, R. Stepien, M. R. Taghizadeh, "Large diameter nanostructured gradient index lens", Opt. Ex. 20 11767 (2012). CrossRef R. Stepien, J. Cimek, D. Pysz, I. Kujawa, M. Klimczak, R. Buczynski, "Soft glasses for photonic crystal fibers and microstructured optical components", Opt. Eng. 53, 071815 (2014). CrossRef A. Filipkowski, B. Piechal, D. Pysz, R. Stepien, A. Waddie, M. R. Taghizadeh, R. Buczynski, "Nanostructured gradient index microaxicons made by a modified stack and draw method", Opt. Lett. 40, 5200-5203 (2015). CrossRef